PENGELOLAAN BIAYA OPERASIONAL LAZNAS SURABAYA - Dania Ulfah Dianti; Noven Suprayogi (Universitas Airlangga, 2018)
This research aims to analyze operating costs in LAZNAS Surabaya, and their strategy to managing LAZNAS‟s amil‟s right. Management is qualitatitave disclosure including Planning, Organizing, Directing, and Controlling. The research method used descriptive qualitative approach with study case strategy on three LAZNAS Surabaya which are LAZNAS Yatim Mandiri, LAZNAS LMI, and LAZNAS Nurul Hayat. Data collected by interview and documentation, Validation techniques used source and technic triangulation. Analysis technique used Spradley. Result of this research is the planning starts with budgeting withapriory method and followed by the planning of receipt of fund and the arrangement of Infaq‟s Amil‟s right. Organizing is using centralitation and decentralitation. LAZNAS without business unit is using centralization, LAZNAS with business unit is using decentralitation. The Controlling Process is by selecting of uneffiecient budget, and their Controlling Action with cross subsidies and saving reserve funds.REFERENCESAl-Zuhayly, Wahbah. 2000. Zakat Kajian Berbagai Mazhab. Bandung. PT. Remaja Rosdakarya.as-Sijistani, Abu Da'ud Sulaiman ibn Ash`ath al-Azadi. Sunan Abu Daud juz 2 hal. 119, hadits no. 1635. Beirut: al-Maktabah al-‘Ashriyah.Amrullah, dan Haris Budiyono. 2004. Pengantar Manajemen. Yogyakarta: Graha IlmuBlocher, Edward J., Kung H Chen, Thomas W. Lin. 2001. Manajemen Biaya dengan Tekanan Stratejik. Salemba Empat. JakartaHarahap. Sofyan Syafri. 2001. Budgeting Penganggaran: Perencanaan Lengkap Untuk Membantu Manajemen, Edisi 1, PT. Raja Grafindo, Jakarta Koontz, Harold dan Heinz Weihrich. 2012. Essentials of Management An International and Leadership Perspective. New Delhi. Tata McGraw-HillNainggolan, Pahala. 2012. Manajemen Keuangan Lembaga Nirlaba. Jakarta: Yayasan Bina Integrasi Edukasi (YBIE)Qardhawi, Yusuf, DR. 1999. Fiqih Az-Zakat, Bandung : MizanSudirman, 2007. Zakat Dalam Pusaran Arus Modernitas, Malang: UIN Malang Press, Solihin, Ismail. 2009. Pengantar Manajemen. Jakarta: ErlanggaSugiyono. (2009). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: AlfabetaSupriyono, RA. 2000. Sistem Pengendalian Manajemen. Buku 2. Edisi Pertama. BPFE. Yogyakarta.Republik Indonesia. 2011. Undang-Undang No. 23 Tahun 2011 Tentang Pengelolaan Zakat. Lembaran Negara RI Tahun 2011, No. 115. Sekretariat Negara. Jakarta.Robbins, Stephen P. 2001. Essentials of Organization Behavior (5th ed.). International Edition: McGraw-Hill, Inc.Wahyu, Marifka Hidayat. 2014. Umat Islam Baru Zakat Sebesar 1 Persen. (Online) (http://gaya.tempo.co diakses pada tanggal 6 Juli 2017)